Bone improvement in osteoporotic rabbits using CoCrMo implants - Zuchuat, Jésica Itatí (2024)
The management of bone repair in patients with osteoporosis depends on the clinical situation and the extent of the damage. The repair of bone lesions by inducing new bone formation is important for maintaining bone architecture and density. Herein, we reported the use of Cobalt Chromium Molybdenum (CoCrMo) implants in osteoporotic rabbits and the regenerative outcomes in vivo. The aim was to determine whether the placement of CoCrMo plates would induce qualitative and quantitative differences in the osteoporotic tissue beneath and surrounding the implant. We assessed the effect of the alloy in the bone of animals receiving implants for 4 and 8 weeks and compared the results to those of the osteoporotic non-implanted bone and the healthy controls. After 4 weeks, minimal histological changes were observed, whereas after 8 weeks a marked osteogenesis was evident with both apposition and substitution of new bone. In addition, a greater number of Haversian canals with increased canal area and decreased intracortical pores were observed in the implanted vs non implanted limb for both experimental groups. We show for the first time that the use of CrCoMo plates induces bone formation under osteoporotic conditions. The beneficial effect is localised on the cortical bone in areas in contact with the material. Although this effect may not directly influence the OP disease itself, it has direct implications for new bone formation adjacent to the biomaterial. This potential enhancement could play a crucial role in improving implant fixation in compromised bone, offering increased biocompatibility and stability.